HAK ASASI MANUSIA TERSANGKA TINDAK PIDANA TERORISME: STUDI PERBANDINGAN ANTARA INDONESIA DAN MALAYSIA - Adesta, Fayez Ghazi Mutasim, Mr.; Priyanto, Sapto, Dr. (Journal of Terrorism Studies, 2022)
Terrorism is the use of force or threat to use force with the aim of bringing a political change, this is the definition according to Brian Jenkins. It is not doubted by anyone that the crime of terrorism is an act of crime that is extraordinary. However, similar to any other crimes, the principle of innocent until proven guilty should always be upheld. This is due to the fact that we should presume anyone’s innocence until the court of law hold otherwise. This paper is aimed to further discuss pertaining to the human rights of an accused of crime of terrorism both in Indonesia and in Malaysia based on terrorism laws of both countries, namely, Law Number 5 of the Year 2018 and Security Offences (Special Measures) Act 2012 (SOSMA) & Prevention of Terrorism Act 2015 (POTA).